Empowering Micro-Entrepreneurs Through Strengthening the Pexita Community in Bekasi City - Nurfadhisa Nurfadhisa; Wa Ode Zusnita Muizu; Siti Chaerani Djen Amar (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
Micro-enterprises face structural challenges such as limited business legality, low managerial capacity, and restricted market access. These issues indicate the absence of community-based mechanisms that consistently strengthen micro-entrepreneurs' capabilities, particularly in urban settings. This study aims to examine the role of the Skilled and Trusted Entrepreneur Expo (PEXITA) community in empowering micro-entrepreneurs and to formulate strategic directions for strengthening the community using SWOT analysis. A qualitative approach with a case study design was employed to explore the dynamics of social learning, network-based support, and experiential marketing practices within the community. Data were collected through in-depth interviews, direct observations during expo activities, and documentation analysis. The findings show that PEXITA functions as a learning ecosystem that enhances members' technical skills, confidence, and market connections through hands-on involvement in expo events. Managerial capacity and business legality remain substantial challenges, accompanied by the community's dependence on core leaders. The SWOT analysis identifies strategic directions related to administrative strengthening, utilization of external networks, and improvement of organizational governance. This study reinforces the strategic relevance of community-based initiatives for micro-enterprise empowerment and offers a conceptual foundation for developing sustainable community-strengthening models in urban contexts.